Enhancing surface functionalization of activated carbon using amino acids from natural source for CO2 capture - Nur Syahirah, Mohamed Hatta *; Farihahusnah, Hussin *; Gew, Lai Ti *; Mohamed, Kheireddine Aroua * (Elsevier, 2023)
Amino acids-functionalized solid porous materials are promising adsorbents for CO2 capture but could not be considered economically viable for large scale application. This study investigated the feasibility of utilizing egg white as an alternative cheap source to commercial amino acids, as a surface modifier to enhance the adsorption capacity of palm shell activated carbon. The adsorbent was successfully prepared via facile activation process and was evaluated for its CO2 adsorption capacity using a fixed-bed column system. The effects of egg white loading, impregnation ratio, adsorption temperature, feed gas flow rate and CO2 inlet concentration were examined. The best sample prepared with 10 wt.% of egg white (ACEW-10) exhibited remarkable CO2 uptake enhancement by 76%, at 25 °C and 1 atm. Characterization study performed using scanning electron microscope, surface area and pore volume analyzer, elemental analyzer, Fourier transform infrared spectroscopy, temperature programmed desorption and thermogravimetric analysis evidently showed that increase in CO2 adsorption capacity was attributed to the introduction of amide functional group of egg white on the surfaces of activated carbon. The adsorbent demonstrated good recyclability over five consecutive adsorption–desorption cycles with >93% regeneration efficiency. All findings indicate that egg white-impregnated activated carbon is a promising green adsorbent for CO2 capture which further allows for potential reutilization of egg white industrial wastes. This research also aims to attract more researchers to explore on other possible natural sources of amino acids for the development of low-cost, sustainable and eco-friendly CO2 adsorbents.